Tingkat Pengaruh Kepuasan Gaji dan Kepuasan Kerja sebagai Mediator Hubungan Antar Keadilan Organisasional terhadap Niat untuk Pindah Kerja - Ongki Helmi Dinata; Didik Subiyanto; Epsilandri Septyarini (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
This study aims to analyze Pay Satisfaction and Job Satisfaction’s Level of Influence as a Mediator of the Reliationship Between Organizational Justice and Turnover Intention at Yogyakarta Industry and Trade Office. The population and sample in this study is 50 Respondent using saturated sampling technique. Data collected utilizing a questionnaire. The result showed that organizational justice has positive significant effect on pay satisfaction and job satisfaction, while organizational justice, pay satisfaction, dan job satisfaction has negative signification effect on turnover intention. The result from sobel test showed that pay satisfaction and job satisfaction unable to mediate the influence of organizational justice on turnover intention at Yogyakarta Industry and Trade office.